Customers' bank selection criteria : the case of Maldives - Shaugee, Ibrahim (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2012)
Studies on bank selection criteria as well as knowledge level of banking principles and its effects on patronization have been done by numerous researchers in various countries. However, review of prior literature has turned up no evidence of such a study having been done in Maldives. Therefore, this study attempts to identify and rank the bank selection criteria perceived as significant by Maldivian banking customers. In addition to this, the study also attempts to categorize the level of awareness and understanding Maldivian banking customers possessed about Islamic banking, its principles and products. Furthermore, attempts are also made to determine whether there is any relationship between the level of Islamic banking knowledge and the decision to patronize Maldives Islamic Bank. The study involved a selfadministered survey, with a sample of 398 respondents. Friedman's test, Pearson's chi-square test and factor analysis was carried out on the data. The results of the analysis show that Maldivian banking customers are able to differentiate between various bank selection criteria and have a perceived ranking of these factors according to its significance to them. The results further show that Maldivian banking customers value trustworthiness followed by availability of automated teller machines and cards above all the other criteria. Furthermore, evidence show that Maldivian banking customers are highly aware of existence of Islamic banking but posses an average level of understanding of its principles. This understanding is especially poor when it comes to specific products. Similarly, there is also evidence of a relationship between customers' Islamic banking knowledge level and their decision to patronize Maldives Islamic Bank.